Staff payroll using image capture and GPS location (SPICG) - Tatccayani, Ravindran (2019)
The usage of technology as business solution is becoming very common which we can see that many organization nowadays make use of technology in their organization. However, there are few organization, especially whom with small budget still using manual paper system to keep track their staff attendance. Unfortunately, the staffs’ salary are calculated based on the handwritten paper record. Due to the reasons that manual system is time consuming and always inaccurate, this project proposed a mobile application attendance with image capture and GPS location named as Staff payroll with Image capture and GPS location (SPICG). This mobile application will authenticate the attendance using image capture and record the staffs’ attendance by locating their position using GPS location. Based on the attendance, the employer will calculate the staff’s payroll. In addition, this project also providing a feature for them to fill in the organization’s sales. Thus, this application can help organization to eliminate the error and prevent fraud attendance by the staffs while improving the processing time.